Where to Sit? Type of Sitting Matters for the Framingham Cardiovascular Risk Score - Katja Borodulin; Tommi Vasankari; Heini Wennman (AIMS Press, 2016)
Background: Current evidence on associations of type-specific sedentary behavior with cardiovascular disease (CVD) is limited to mainly screen-time sedentary behavior (SB). We aimed to study the associations of type-specific and total time spent sitting with the Framingham 10-year cardiovascular disease risk score (Framingham score) in Finnish adults. Methods: Data comprise the National FINRISK 2007 and 2012 health examination surveys with 10,185 participants aged 25-74 years, apparently free of CVD. Participants reported average daily time spent sitting in different locations: work-related sitting, at home in front of television (TV), at home in front of computer, in a vehicle, and elsewhere. Total SB time was calculated from these context-specific self-reports. Accelerometer-based sedentary time was assessed in 988 FINRISK 2012 participants. Framingham score was calculated using information on blood pressure and its medication, cholesterol levels, age, diabetes status, and smoking. Analyses were adjusted for age, study year, education, employment status, leisure time physical activity, and body mass index. Results: Out of several type-specific sitting behaviors, only TV sitting showed systematic associations with the Framingham score in both genders. The lowest Framingham risk was found for TV sitting from 6 minutes to less than 1 hour daily. Of other types of sitting, computer sitting was inversely associated with the Framingham risk in men only. Total self-reported sitting time did not show significant associations with the Framingham score, but instead higher objectively assessed sedentary time showed higher Framingham risk in men. Conclusions: TV sitting showed most systematic associations with CVD risk score. This suggests that of all types of SB, reducing TV sitting should be targeted for reducing CVD risk.